DdrB Protein, an Alternative Deinococcus radiodurans SSB Induced by Ionizing Radiation - Norais, Cédric A. (American Society for Biochemistry and Molecular Biology, 2009)
Deinococcus radiodurans exhibits an extraordinary resistance to the effects of exposure to ionizing radiation (IR). DdrB is one of five proteins induced to high levels in Deinococcus following extreme IR exposure and that play a demonstrable role in genome reconstitution. Although homology is limited, DdrB is a bacterial single-stranded DNA-binding protein. DdrB features a stable core with a putative OB-fold, and a C-terminal segment with properties consistent with other bacterial SSBs. In solution, the protein functions as a pentamer. The protein binds single-stranded DNA but not duplex DNA. Electron microscopy and assays with two RecA proteins provide further structural and functional identification with bacterial SSB. Overall, the results establish DdrB as the prototype of a new bacterial SSB family. Given the role of SSB as a mobilization scaffold for many processes in DNA metabolism, the induction of an alternative and quite novel SSB following irradiation has potentially broad significance for the organization of genome reconstitution functions.